Дослідження динамічного сайту для кафе - Валюх, Д. М. (ХНУРЕ, 2024)
This work is built around a fictional business case. The business case provides a way to explore cloud-computing topics in the context of relatable business needs. This scenario is intended to provide an example of the real world applicability of researched technical concepts. In this work, an application was deployed on an Amazon Elastic Compute Cloud (Amazon EC2) instance. The application enables the café to accept online orders. After testing that the application worked as intended in the first AWS Region (the development environment), then an Amazon Machine Image (AMI) was created from the EC2 instance. A second instance of the same application was also deployed as the production environment in another AWS Region.
Keywords: сайту для кафе; кафе